The Effect of Institutional Quality on Economic Growth: Evidence from Tripartite Approaches in the Context of War-Torn Countries - Aden Dirir, Sadik (Organizations and Markets in Emerging Economies, 2023)
This paper is undertaken to investigate the role of institutional quality in proportion to the economic growth of war-torn countries during the last 20 years. Within this framework, the paper employed three different models to investigate the link that exists between good governance indicators and economic growth. According to the results, the long-run PMG model indicated that political stability and regulatory quality increase war-torn countries’ economic development. Contrarily, it has been demonstrated that the situation of law and corruption in these countries reduces economic growth. Neither the long-term nor short-term estimations from the MG and DFE models showed any noteworthy results. Next, the FMOLS and DOLS revealed that political stability, voice and accountability have a favorable effect on the economic development of these nations. On the other hand, these nations’ regulatory standards had a very detrimental impact on economic growth. Lastly, the fixed-effects model showed that a 1% improvement in these nations’ political stability will result in a 4.5% increase in GDP. This research will aid managers, academics, and policymakers in determining the course of actions needed in their areas of specialization or nations of interest to ensure economic growth and put in place an effective institutional framework through enforced supervision.
Keywords: Governance; Institutional quality; Economic growth; War-torn countries